2014
DOI: 10.3892/ijmm.2014.1890
|View full text |Cite
|
Sign up to set email alerts
|

Bone mesenchymal stem cell transplantation via four routes for the treatment of acute liver failure in rats

Abstract: In the present study, we assessed the efficiency of four BMSC transplantation methods as a therapy for liver failure. A rat model (80 Sprague-Dawley rats) of D-galactosamine (D-gal)/lipopolysaccharide (LPS)-induced acute liver failure (ALF) was established and the rats were divided into 5 groups: a hepatic artery injection group, a portal vein injection group, a vena caudalis injection group, an intraperitoneal injection group and a control group (16 per group). Following transplantation, the liver tissue and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 50 publications
2
38
0
3
Order By: Relevance
“…The chemokine stromal cell-derived factor-1 (SDF-1) binds to CXCR4. Numerous studies have reported that SDF-1 is critical for stem/progenitor and mesenchymal cell chemotaxis and inflammatory cell homing to injured tissue via interaction with CXCR4 on the surface of these cells; CXCR4 maybe highly expressed in humans and mice following chemotaxis along an SDF-1 gradient (24,25). This indicates that the level of CXCR4 expression may reflect the activation of the SDF-1/CXCR4 axis, which is associated with stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine stromal cell-derived factor-1 (SDF-1) binds to CXCR4. Numerous studies have reported that SDF-1 is critical for stem/progenitor and mesenchymal cell chemotaxis and inflammatory cell homing to injured tissue via interaction with CXCR4 on the surface of these cells; CXCR4 maybe highly expressed in humans and mice following chemotaxis along an SDF-1 gradient (24,25). This indicates that the level of CXCR4 expression may reflect the activation of the SDF-1/CXCR4 axis, which is associated with stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, recent studies in rats have also found that MSC infusion via portal vein is more beneficial than caudal vein with regards to MSC "homing" and improvement of liver function . In a study by Sun et al (2014) which compared four different routes of bone marrow (BM)-MSC transplantation in a rat model, portal vein administration was found to have greater impact on stem cell "homing" than the other routes (Sun et al, 2014). Furthermore, portal vein was the best route for transplanting MSCs and improved rat liver function compared to hepatic artery, peripheral vein or intrahepatic routes (Sang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relationship between transplantation route and transplantation efficacy is unclear [15]. In the present study, we injected BM-MSCs through two different routes (intravenous and intrasplenic) and compared their efficacy for the management of CCl 4 -induced liver fibrosis and also assessed the conceivable mechanisms underlying this effect.…”
Section: Discussionmentioning
confidence: 99%